Pemberdayaan Kelompok Wanita Tani Melalui Penyuluhan Dan Pelatihan Budidaya Aquaponik - Rasmani, Upik Elok Endang; Haqqulimara, Bia; Chaerunisa, Rahmah; Saputri, Meliana; Rahmadapasha, Laela; Khairina, Rissa; Safira Nur'aini, Novian; Setyowati, Dani; Rahayu Ningsih, Etie; Aviani, Lia (DEDIKASI: Community Service Reports, 2023)
The COVID-19 pandemic has had an impact on all walks of life. One of them is in the economic sector, which can be seen from the instability of food prices so that it adds to the financial burden of the community. Aquaponics is one way to achieve food security as well as an alternative solution for people who are constrained by limited land. This community service activity aims to introduce cultivation with a mutually beneficial combination of aquaculture and hydroponic systems using aquaponic techniques, explain the benefits and future prospects obtained from aquaponics, explain how to make aquaponic media using buckets, explain how to treat it to empower Women's Groups Farmers to have soft skills and insight into the world so that they can use vacant land to become food gardens, in addition to personal consumption can also be used as a source of income. The participation and enthusiasm of the participants in the aquaponics counseling and training consisting of members of the Sekarsari Farmer Women's Group in Dusun Beran was very good. The participants were enthusiastic and actively asked questions in aquaponics counseling. This activity succeeded in pleasing the community that aquaponic cultivation techniques are more effective, become an alternative solution to limited land, as a means to fill spare time, as well as personal consumption and income. Extension activities and aquaponic cultivation training are useful and are expected to be implemented in a sustainable manner.